UJI ANTI BAKTERI BERBAGAI MACAM EKSTRAK DAUN GANDARUSA(JUSTICIA GENDARUSSA BURM. F) TERHADAP BAKTERI AEROMONAS HIDROPHYLLA - Pitay A. D. E. Fonny; J. L. Risamasu; Yuliana Saloso (Nusa Cendana University, 2018)
Abstract - The use of medicinal plants as an anti-bacterial ingredient develops in line with increasing fish disease, Aeromonas hidrophylla is one of the bacteria causing dangerous diseases in freshwater fish cultivation. This research aims to know various kinds of gandarusa leaf extract in inhibiting bacterium Aeromonas hidrophylla, for get the proper dosage of the leaves of gandarusa in inhibiting the bacterium Aeromonas hidrophylla and to know the active compound contained in the leaves of gandarusa, this study used 3 treatments and 3 replications. The results of this study showed that the dried decoction of gandarusa leaves was able to inhibit the bacterium Aeromonas hydrophylla, a 1 g treatment is capable of inhibiting the bacterium Aeromonas hidrophylla with an inhibitory zone of 11.33 mm and the active compound contained in the leaf gandarusa are alkaloids, flavonoids, terpenoids and tannins. Based on the results obtained that the dried stew of gandarusa leaves able to inhibit the growth of Aeromonas hydrophylla bacteria. Therefore, the authors expect to do further research in order to determine whether the dried stew of gandarusa leaves can inhibit the growth of Aeromonas hydrophylla bacteria that attack freshwater fish Keywords: Anti Bacterial, Gandarusa Leaf, Aeromonas hydrophylla, Activ Compound